Prokalcitonin in interlevkin-6 v diagnostiki hude okužbe pri otrocih s febrilno nevtropenijo - Kitanovski, Lidija (Zdravniški vestnik, 2004)
Background. The results of the study conducted to determine whether procalcitonin (PCT) and interleukin-6 (IL-6) are more sensitive and specific markers of severe infection in children with febrile neutropenia (FN) than routinelly used C-reactive protein (CRP) are presented in the article. 68 episodes of FN experienced by 32 patients were divided into three groups according to the site of infection. Group 2: episodes of bacteraemia and/or clinical sepsis (n = 16), group 2: episodes offocal infection (n = 16) and group 3: episodes of fever of unknown origin (FUO) (n = 36). Blood samples forfurther PCT and IL-6 determination were collected on three consecutive days. CRP concentrations were measured daily in each patient until the resolution of fever. PCT, IL-6 and CRP concentrations were measured on one occassion in each of the 18 afebrile patients with malignant disase forming the reference group. Serum PCT and IL-6 concentrations were measured by immunochemiluminometric and immunoenzymatic assay. Receiver Operating Characteristic (ROC) curves were used to determine optimum sensitivity, specificity, positive and negative predictive values and diagnostic accuracy of the studied parameters. Conclusions. PCT and IL-6 were found to be earlier and more sensitive markers of severe infection in neutropenic patients than CRP. The erliest one was IL-6 followed by PCT and CRP. Sequential determination of PCT up to 72 hours improved its diagnostic value, which was not the case for IL-6.In patients with gramnegative bacteraemias PCT concentracions were 3-5 times higher comparing to grampositive, whereas IL-6 concentrations were comparable in both groups.
Keywords: Bacteremia; Bakteriemija; Blood; Calcitonin; Child; C-Reactive Protein; C-reaktivna beljakovina; Fever Of Unknown Origin; Interleukin-6; Interlevkin-6; Kalcitonin; Neoplasms; Neutropenia; Nevtropenija; Novotvorbe; Občutljivost in specifičnost; Otrok; Sensitivity And Specificity; Sepsa; Sepsis; Vročica nejasnega izvora